Cerebrospinal Fluid Pressure Dynamics as a Bedside Test in Traumatic Spinal Cord Injury to Assess Surgical Spinal Cord Decompression: Safety, Feasibility, and Proof-of-Concept. (April 2023) - Kheram, Najmeh; Boraschi, Andrea; Pfender, Nikolai; Friedl, Susanne; Rasenack, Maria; Fritz, Benjamin; Kurtcuoglu, Vartan; Schubert, Martin; Curt, Armin; Zipser, Carl M.
Background: Sufficient and timely spinal cord decompression is a critical surgical objective for neurological recovery in spinal cord injury (SCI). Residual cord compression may be associated with disturbed cerebrospinal fluid pressure (CSFP) dynamics. Objectives: This study aims to assess whether intrathecal CSFP dynamics in SCI following surgical decompression are feasible and safe, and to explore the diagnostic utility. Methods: Prospective cohort study. Bedside lumbar CSFP dynamics and cervical MRI were obtained following surgical decompression in N = 9 with mostly cervical acute-subacute SCI and N = 2 patients with non-traumatic SCI. CSFP measurements included mean CSFP, cardiac-driven CSFP peak-to-valley amplitudes (CSFPp), Valsalva maneuver, and Queckenstedt's test (firm pressure on jugular veins, QT). From QT, proxies for cerebrospinal fluid pulsatility curve were calculated (ie, relative pulse pressure coefficient; RPPC-Q). CSFP metrics were compared to spine-healthy patients. computer tomography (CT)-myelography was done in 3/8 simultaneous to CSFP measurements. Results: Mean age was 45 ± 9 years (range 17-67; 3F), SCI was complete (AIS A, N = 5) or incomplete (AIS B-D, N = 6). No adverse events related to CSFP assessments. CSFP rise during QT was induced in all patients [range 9.6-26.6 mmHg]. However, CSFPp was reduced in 3/11 (0.1-0.3 mmHg), and in 3/11 RPPC-Q was abnormal (0.01-0.05). Valsalva response was reduced in 8/11 (2.6-23.4 mmHg). CSFP dynamics corresponded to CT-myelography. Conclusions: Comprehensive bedside lumbar CSFP dynamics in SCI following decompression are safe, feasible, and can reveal distinct patterns of residual spinal cord compression. Longitudinal studies are required to define critical thresholds of impaired CSFP dynamics that may impact neurological recovery and requiring surgical revisions.